2018
DOI: 10.1071/an16687
|View full text |Cite
|
Sign up to set email alerts
|

Influence of low-protein and low-amino acid diets with different sources of protease on performance, carcasses and nitrogen retention of broiler chickens

Abstract: A 42-day experiment was conducted with 625 1-day-old male Hubbard chickens to evaluate the performance, carcass traits, nitrogen retention and economics of broiler chickens fed low protein and amino acid diets supplemented with different protease sources. Treatments included positive (PC) and negative (NC) controls (PC at 19.3% protein vs NC at 18.8% protein), with NC containing 7% less digestible amino acids. The other three treatment groups were based on the NC diet supplemented with 0.05% Cibenza® DP100 (CB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
27
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 23 publications
7
27
3
Order By: Relevance
“…In this study, an extreme reduction (6%) of dietary protein and digestible amino acids negatively affected FCR, although, when protease was added, the growth performance results were similar to the standard diets. Rehman et al (2017) also observed a decrease in body weight of broilers fed diets with protein reduction, and it was associated to the low dietary protein and amino acid concentrations. These authors obtained better results of performance, feed utilization, carcass traits, and nitrogen retention when there was reduction of protein with protease supplementation.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, an extreme reduction (6%) of dietary protein and digestible amino acids negatively affected FCR, although, when protease was added, the growth performance results were similar to the standard diets. Rehman et al (2017) also observed a decrease in body weight of broilers fed diets with protein reduction, and it was associated to the low dietary protein and amino acid concentrations. These authors obtained better results of performance, feed utilization, carcass traits, and nitrogen retention when there was reduction of protein with protease supplementation.…”
Section: Discussionmentioning
confidence: 83%
“…The protease used in this study was previously shown to enhance proteins, AAs and energy digestibility in broilers fed different protein levels [ 12 ]. Therefore, the observed improvements in nutrient digestibility and nutrient retention [ 15 , 17 , 22 ] in birds fed diets containing exogenous protease may have beneficial effects on body weight. This finding is in accordance with those reported by Angel et al [ 11 ] and Mahmood et al [ 10 ], where supplementation of mono-component protease improved growth performance in broilers.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, supplemental protease in the diet from 1 to 14 days had no effect on body weight gain, feed intake, and feed efficiency of chickens fed soybean-meal diets [32,33]. Cowieson et al also failed to observe, on days 7-14, a protease effect on bird body weight gain and feed intake, but protease appeared to increase the gain to feed ratio [34].…”
Section: Growth Performancementioning
confidence: 93%
“…Cowieson et al also failed to observe, on days 7-14, a protease effect on bird body weight gain and feed intake, but protease appeared to increase the gain to feed ratio [34]. Interestingly, in all of these studies, a positive effect of protease on body weight gain and feed efficiency was observed after 14 days [32][33][34]. This indicates that exogenous protease efficacy can be impacted by the age of the birds.…”
Section: Growth Performancementioning
confidence: 95%